Challenges in assessing national radiotherapy costs: application of the ESTRO-HERO model in Spain - Corral, Julieta; Algara, Manel; Muñoz-Montplet, Carles; Eraso, Arantxa; Giralt, Jordi; Defourny, Noémie; Lievens, Yolande; Borras, Josep Maria (Frontiers in Public Health, 2024)
Background and purposeThe aim was to estimate the cost of the external beam radiotherapy (EBRT) in public health care centers in Catalonia (Spain), according to the ESTRO-HERO costing model for 2018.Materials and methodsPersonnel, equipment, and activity data from 2018 from the 11 RT centers were used, incorporating European mean values adapted to the Catalan context. Secondly, EBRT costs were estimated, incorporating 2023 fractionation technique and scheme usage percentages. Finally, complementary estimates were included: complementary planning examinations, stereotactic body radiation therapy (SBRT) fiducial markers, and hospital overhead costs.ResultsIn 2018, EBRT cost was estimated at EUR 42.2 M for all patients in the region. Directly related treatment activities represented 69.0% of the total cost, while support and non-directly related EBRT activities accounted for 20.2 and 10.8%, respectively. Mean radical treatment cost varied from €1714 (leukemia) to €4,645 (pancreas), and for palliative intent, from €938 (bone metastases) to €1753 (brain metastases). According to the technique used, costs ranged from €1,475 (3D conformal) to €3,608 (rotational IMRT), and by fractionation scheme, from €1,308 (extreme hypofractionation) to €4,094 (standard fractionation). Accounting for 2023 complexity levels, mean treatment cost rose by 0.9%, but varied widely by tumor site, with a 13% increase for stomach cancer, and decreases of −15.0, −24.4, and − 17.2% in myeloma, pancreas, and lung cancer, respectively. Including complementary examinations and hospital overhead costs, mean cost increased by 15.6%.ConclusionThis study provides a first approximation to EBRT cost using time-driven activity-based costing (TD-ABC) in Catalonia showing the feasibility of the assessment. For each indication, average treatment cost increases with the associated complexity. Additionally, costs decrease with hypofractionation schemes, largely due to lower equipment weight in treatment cost. Consequently, the adoption of stereotactic techniques is driving cost decreases. Overall, this model represents a robust tool for analyzing different possible scenarios, including changes in fractionation and complexity.